Tromboprofilaxis farmacológica en pacientes oncológicos quirúrgicos en el Hospital Clínico de la Universidad de Chile - Rodríguez G., Cinthya; Rodríguez C., Lidia; Figueroa M., Gastón; Gazitúa P., Raimundo; Conte L., Guillermo (Revista Hospital Clínico Universidad de Chile, 2015)
Background: The aim of this study is to evaluate the use of thromboprophylaxis in surgical oncology patients in HCUCH in 2011. Method: Retrospective analysis of patients with cancer undergoing surgery in 2011. Was defined as adequate pharmacological thromboprophylaxis the correct dose, mechanical prophylaxis in case of drug contraindications and beginning on day 0 or 1. Results: 131 medical records were reviewed. Main neoplasms were colorectal (21.3 %), prostate (12.9 %), gallbladder (8.3 %) and stomach (6.9 %). Of the patients requiring pharmacologic thromboprophylaxis (n = 110) were rated as adequate 52 patients (47 %), 47 inadequate (43 %) and 11 absent (10%). The causes of inappropriate use of pharmacological thromboprophylaxis included 27 late onset (58 %), 10 lower doses (21 %), 3 late onset associated with lower dose (6 %), 6 incomplete thromboprophylaxis (13%) and 1 dose increased (2%). Factors significantly associated with pharmacological thromboprophylaxis absent were: <40 years of age (p = 0.002), head and neck cancer (p < 0.001), and hospital stay <7 days (p < 0.001). Conclusions: The absence of pharmacological thromboprophylaxis is associated with lower absolute risk factors for VTE: Age less than 40 years old, head and neck cancer, hospital stay less than 7 days.